Hubungan Motivasi Belajar dengan Hasil Belajar Daring Geografi di Masa Pandemi Covid-19 - Maddatuang Maddatuang; Suprapta Suprapta; Asdar Asdar (UNIVERSITAS NEGERI MAKASSAR, 2022)
There has been a massive change in the learning system in the era of the Covid-19 pandemic which is characterized by the implementation of online learning. However, on the other hand, online learning must pay attention to the condition of learners related to learning motivation during the covid-19 pandemic. In this study, researchers wanted to know the relationship of student motivation levels with geography learning outcomes in online learning in the Covid-19 period which was held at SMAN 8 Maros. This research belongs to the ex post facto type of research. Independent variable data is obtained using a questionnaire using the likert scale and depenent variables are collected by documentation methods. Research results show that 1) the level of motivation of learners falls into the high category; 2) The average geography learning outcome of students falls into sufficient categories; 3) There is a relationship between student learning motivation and student learning outcomes.AbstrakTerjadi perubahan besar-besaran pada sistem pembelajaran di era pandemi Covid-19 yang ditandai dengan diterapkannya pembelajaran daring. Namun, disisi lain pembelajaran daring mesti memperhatikan kondisi peserta didik terkait motivasi belajar selama pandemi covid-19. Sehingga pada penelitian ini peneliti ingin mengetahui hubungan tingkat motivasi belajar siswa dengan hasil belajar geografi pada pembelajaran daring dimasa Covid-19 yang diakan di SMAN 8 Maros. Penelitian ini termasuk kedalam jenis penilitian ex post facto. Data variabel independen didapatkan dengan menggunakan angket menggunakan skala likert dan variabel depenen dikumpulkan dengan metode dokumentasi. Hasil peneiltian menunjukkan bahwa 1) tingkat motivasi peserta didik termasuk dalam kategori tinggi; 2) rata-rata hasil belajar geografi siswa masuk dalam kategori cukup; 3) terdapat hubungan motivasi belajar siswa dengan hasil belajar siswa.